2022
DOI: 10.3390/s22020542
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Approach for Automatic Microaneurysms Detection

Abstract: In diabetic retinopathy (DR), the early signs that may lead the eyesight towards complete vision loss are considered as microaneurysms (MAs). The shape of these MAs is almost circular, and they have a darkish color and are tiny in size, which means they may be missed by manual analysis of ophthalmologists. In this case, accurate early detection of microaneurysms is helpful to cure DR before non-reversible blindness. In the proposed method, early detection of MAs is performed using a hybrid feature embedding ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Additionally, it was observed that our model's classification performance improved when the extracted features were subjected to a frequency and spatial channel attention approach. Mateen et al, 25 and Quellec et al, 26 along with the idea of channel attention, the proposed framework was further optimized using the back propagation algorithm by updating weights and bias. Feed‐forward, backward, combining all the values, and calculating the updated weight value are the steps in backpropagation.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it was observed that our model's classification performance improved when the extracted features were subjected to a frequency and spatial channel attention approach. Mateen et al, 25 and Quellec et al, 26 along with the idea of channel attention, the proposed framework was further optimized using the back propagation algorithm by updating weights and bias. Feed‐forward, backward, combining all the values, and calculating the updated weight value are the steps in backpropagation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it provides high f-measure and low specificity. Mateen et al (2022) have presented deep learning approach for automatic MA detection. The suggested method uses VGG-19 and Inception-v3 pre-trained CNN models in a hybrid feature embedding approach to perform early identification of MAs.…”
Section: Related Workmentioning
confidence: 99%
“…Computer vision approaches for image processing help automation specialists create computer-assisted diagnostic systems (CADSs) [50] that improve diagnosis accuracy in contemporary ophthalmology [51][52] [53]. Standard processes must therefore be developed in order to ease into conventional ways because computer algorithms and methods are used in imaging analysis.…”
Section: B Related Workmentioning
confidence: 99%